Soil versus foliar iodine fertilization as a biofortification strategy for field-grown vegetables - Lawson, Patrick G.; Daum, Diemo; Czauderna, Roman; Meuser, Helmut; Härtling, Joachim W. (Frontiers in Plant Science, 2015)
Iodine (I) biofortification of vegetables by means of soil and foliar applications was investigated in field experiments on a sandy loam soil. Supply of iodine to the soil in trial plots fertilized with potassium iodide (KI) and potassium iodate (KIO3) directly before planting (0, 1.0, 2.5, 7.5 and 15 kg I ha-1) increased the iodine concentration in the edible plant parts. The highest iodine accumulation levels were observed in the first growing season: In butterhead lettuce and kohlrabi the desired iodine content [50 - 100 µg I (100 g FM)-1] was obtained or exceeded at a fertilizer rate of 7.5 kg IO3--I ha-1 without a significant yield reduction or impairment of the marketable quality. In contrast, supplying KI at the same rate resulted in a much lower iodine enrichment and clearly visible yield reduction. Soil applied iodine was phytoavailable for a short period of time as indicated by a rapid decline of CaCl2-extractable iodine in the top soil. Consequently, long-term effects of a one-time iodine soil fertilization could not be observed. A comparison between the soil and the foliar fertilization revealed a better performance of iodine applied aerially to butterhead lettuce, which reached the desired iodine accumulation in edible plant parts at a fertilizer rate of 0.5 kg I--I ha-1. In contrast, the iodine content in the tuber of sprayed kohlrabi remained far below the targeted range. The results indicate that a sufficient spreading of iodine applied on the edible plant parts is crucial for the efficiency of the foliar approach and leafy vegetables are the more suitable target crops. The low iodine doses needed as well as the easy and inexpensive application may favor the implementation of foliar sprays as the preferred iodine biofortification strategy in practice.